As noções de integração curricular na Revista Brasileira de Estudos Pedagógicos (1952 ‒ 1964) - Costa, Robson Andrade (2021)
This work aimed to investigate the notions of curricular integration mobilized by the texts published in the Revista Brasileira de Estudos Pedagógicos (RBEP), in the “Ideas and debates” section, between 1952 and 1964. The hypothesis that the notions of curricular integration came to be present in the articles of the Journal, largely due to the presence of authors linked to the Escola Nova Movement and to the performance of Anísio Teixeira, then-named president of the National Institute of Educational Studies and Research (Inep) and a notorious advocate of curriculum renewal. The theoretical references used are within the scope of the Social History of the Curriculum, especially in the concept of pre-active curriculum, by Ivor Goodson, which makes it possible to historically situate the process that precedes the constitution of the prescribed curriculum. The presence of notions of curricular integration was identified in texts that thematized the teaching of different subjects, especially associated with the circulation of theories by foreign authors, such as John Dewey, Jean-Ovide Decroly and Willian Kilpatrick. The authors of the investigated texts, however, do not mention Brazilian colleagues, making it difficult to identify a sharing of references and the constitution of a network of interlocutors.